PEMANFAATAN MESIN PENCACAH SAMPAH ORGANIK PORTABEL UNTUK KEPERLUAN RUMAH TANGGA DI KECAMATAN SIMANINDO KABUPATEN SAMOSIR - Hodmiantua Sitanggang; Enzo Wiranta Battra Siahaan (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2021)
Simanindo District is a tourist destination of Lake Toba which is always crowded by foreign tourists thus increasing the amount of waste generated. Community behavior that is less concerned with environmental hygiene becomes another factor causing waste problems. Due to lack of care of the community then the amount of waste for households is also increasing due to the many uses of food scraps and beverages used by every community. From the observation result in Simanindo District with the population of 20190 people with the amount of waste 13 m3 / day assuming that each household produce household waste 0,25 kg / day, then 492,75 kg / day. Where 80% is organic waste, in 1 week there are 2759,4 kg or about 4.75 tons in 1 month. As a miniature of household organic waste management, with approximately 90 families there is 22.5 kg of waste / day. The impact of garbage accumulation is environmental pollution, unflattering scenery, air pollution, soil, and health problems. The solution of the problem is needed a practical tool and efficient to overcome household waste by realizing a portable organic waste enumerator machine Portable organic waste enumerator machine capable of chopping 6 kg / hour of household organic waste such as plant leaves are then used as compost raw material. The goal is to simplify and minimize the volume so it is practical enough to take to the next processing.